2017
DOI: 10.1128/msystems.00061-17
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Phylogenomics of the Lactobacillus casei Group Highlights Taxonomic Inconsistencies and Reveals Novel Clade-Associated Features

Abstract: The closely related species of the Lactobacillus casei group are extensively studied because of their applications in food fermentations and as probiotics. Our results show that many strains in this group are incorrectly classified and that reclassifying them to their most closely related species type strain improves the functional predictive power of their taxonomy. In addition, our findings may spark increased interest in the L. casei species. We find that after reclassification, only 10 genomes remain class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 53 publications
6
98
0
Order By: Relevance
“…html) [32]. The draft genomes of the L. casei strains DS1_13 (GCA_003052865.1), DS13_13 (GCA_003052855.1), FMNP02 (GCA_000814185.1), LC5 (GCA_002192215.1), 867_LCAS (GCA_001066695.1) and L. zeae strains AMBR2 (GCA_900185125.1) [33], B900021 (GCA_001940585.1), CECT 9104 (GCA_900492555.1), HMSC068F07 (GCA_001812525.1), N87 (GCA_001013375.1) used as the reference were downloaded from GenBank. The draft genome size of the 16 strains of L. casei and L. zeae ranged from 2.78 to 3.13 Mbp as indicated in Table S2 together with their other genomic features.…”
mentioning
confidence: 99%
“…html) [32]. The draft genomes of the L. casei strains DS1_13 (GCA_003052865.1), DS13_13 (GCA_003052855.1), FMNP02 (GCA_000814185.1), LC5 (GCA_002192215.1), 867_LCAS (GCA_001066695.1) and L. zeae strains AMBR2 (GCA_900185125.1) [33], B900021 (GCA_001940585.1), CECT 9104 (GCA_900492555.1), HMSC068F07 (GCA_001812525.1), N87 (GCA_001013375.1) used as the reference were downloaded from GenBank. The draft genome size of the 16 strains of L. casei and L. zeae ranged from 2.78 to 3.13 Mbp as indicated in Table S2 together with their other genomic features.…”
mentioning
confidence: 99%
“…In addition, the name L. paracasei , whose type strain was very closely related to the historical L. casei strains, was kept alive. The consequence was that many of the strains that were historically classified to L. casei should now be classified to L. paracasei , and that all strain historically classified to L. zeae should now be classified to L. casei (Wuyts et al 2017) . In this work, we confirmed that the L. casei type strain and the (rejected) L. zeae type strain are closely related, but not so closely that it would be absurd to consider them different species.…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in many misclassifications. For example, we have previously shown that many genomes annotated as Lactobacillus casei on NCBI are in reality more closely related to the Lactobacillus paracasei type strain (Wuyts et al 2017) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, special attention was put into the manual curation of the DAIRYdb sequences at species rank. Despite the genotypic and phenotypic characteristics of the most common LAB in cheese are extensively studied and described, several unresolved controversies regarding the nomenclature of some keystone species still remain unsolved, such as for the species L. helveticus and L. gallinarum, S. thermophilus and S. salivarius, L. casei and L. paracasei and L. zeae, L. plantarum and L. paraplantarum (77)(78)(79). The DAIRYdb is composed of sequences retrieved from the Silva database along with their respective taxonomy, which was manually inspected for nomenclature hierarchy conflicts based on the phylogenetic position within the tree.…”
Section: Curationmentioning
confidence: 99%